Antioxidant capacity, antibacterial activity, and cell cytotoxicity in cholangiocarcinoma (CCA) from Boesenbergia rotunda (L.) Mansf. - Sopitthummakhun, Kittipat; Rattanasinganchan, Panthip; Nimmanee, Panjaphorn; Paungmoung, Porntip; Moonthiya, Penpak; Thitapakorn, Veerachai (Asia-Pacific Journal of Science and Technology, 2021)
Boesenbergia rotunda (L.) Mansf. rhizome was collected during different seasons and cultivation areas, defined as S1, S2, and S3. The rhizome extract was prepared by sequential maceration in hexane, ethyl acetate, and methanol. The rhizome extracts were evaluated for antioxidant, total phenolic and flavonoid content, cytotoxicity against cholangiocarcinoma (CCA), and pathogenic bacteria effects. The S2 extract in hexane and ethyl acetate demonstrated the highest Trolox Equivalent Antioxidant Capacity (TEAC) at 2.650 ± 0.215 and 2.089 ± 0.405, respectively. The highest total phenolic and flavonoid content were found in the S1 and S3 ethyl acetate extracts at 18.187 ± 0.961 mg- Gallic acid Equivalent (GE)/g-Dry Material (DM) and 381.863 ± 18.917 mg-Quercetin Equivalents (QE)/100 g-DM, respectively. The greatest cytotoxicity against CCA was found in the S2 ethyl acetate extract with an IC50 value of 22.65 ± 0.68 mg/mL, however, this did not affect normal cholangiocytes. Moreover, the cytotoxic effect on CCA may have involved apoptosis based on the chromatin condensation and nuclear fragment seen using fluorescence microscopy with 4′,6-diamidino-2-phenylindole staining. The S1 ethyl acetate extract was cytotoxic to gram-positive bacteria. The inhibition zone was 10.5, 9.5, 8.5, and 11.8 mm for Staphylococcus aureus ATCC 25923, Methicillin-resistant S. aureus (MRSA), S. epidermidis, and Bacillus cereus, respectively. In conclusion, this study demonstrated that there are active components in B. rotunda rhizome hexane and ethyl acetate extracts that have antioxidant, anticancer, and antibacterial activities. The active ingredients should be characterized in future studies.